Estudio de factibilidad para la creación de un centro de capacitación profesional en la comuna La Piedadcita - Holguín Míguez, Shirley Lizbeth (2023)
The current investigative work entitled FEASIBILITY STUDY FOR THE CREATION OF A PROFESSIONAL TRAINING CENTER IN LA PIEDADCITA COMMUNITY had the purpose of determining the feasibility of creating a training center, so that a descriptive investigation was carried out. The population was made up of members from La Piedadcita community to whom the survey technique was applied with a questionnaire of previously prepared questions. The main results of the market study showed that there is a wide acceptance for the acquisition of the service that the training center will offer. The 84% of the population is supposed to acquire the service and the 54% would be part of the target market. Some of the offered services are the courses; these last ones are intended to repair the equipment and tools used in the field. In addition, the economic study presents a total initial investment of $3,777.84; as well as the working capital for the first month which is $2,521.84; it covers the expenses incurred in the implements for the initial function, the constitution expenses, and the salaries of the staff. The profits that will be generated with the sale of the courses fluctuate around $35,000.00. On the other hand, the income statement is made to know the profit in the first year which is $6,807.54. Regarding the financial indicators a NPV of $23,853.80 is appreciated and an IRR of 47.72% which supports that the project is viable. The B/C benefit cost ratio was 1.51; it means that for each unit of capital invested, a half is obtained, so resulting in 51% net profit.